CHARACTER BUILDING THROUGH GROWING SPIRITUAL VALUES BASED ON THE QURAN OF SURAH AL-MUZAMMIL VERSES 1-8 - Mariah Zakiyah, Maya (IJBLE Scientific Publications Community Inc., 2023)
Character education in Indonesia is considered a weak because one of the reasons his education is to prioritize cognitive aspects. In contrast, the behavior and feelings of students pay less attention. Furthermore, in the Quran of Surah (Q.S) Al-Muzammil verses 1-8, some teachings can be educated to improve spiritual intelligence. Moreover, the teachings in the letter are not only about the rites of worship but also about the whole required by the feelings, knowledge and actions of humans in society. So from this research, we can know how the spiritual values ​​contained in the Quran of Surah Al-Muzzammil, verses 1-8, can form a person's character. The research method used is a literature study with a hermeneutical approach. Data collection techniques in the form of documentation techniques and documents to be analyzed are the contents of the text of surah Al-Muzzammil verses 1-8. While the data analysis method used is Content Analysis, and In addition to content analysis, because the object of study is in the form of text, then this research also uses technical analysis of semiotic. The result of the literature analysis shows that the spiritual values ​​contained in the Q.S Al-Muzzammil verses 1-8 are commands to do good to others, establish prayer, perform qiyamul-lail, recite qur'an with tartil, and with dhikr to God. All of these teachings are not just as an education to hone spiritual intelligence but also contain four aspects, namely the aspect of the soul, spirit, social and biological so that it can help in enhancing one's intellectual and emotional intelligence including helping in physical health. Spiritual, emotional and intellectual intelligence is the embodiment of one's character.